Bad news, vol. 1, no. 1 - Guglielmo, Bob; Pulga, Jayr; Karasik, Paul 1956-; Head, Glenn 1958-; Farmer, Eric; Newgarden, Mark; Struck, Ken; Wronker, Eytan 1957- (Bad News Press, 1983)
"Started as a SVA class project assigned by Art Spiegelman in order to give his students some practical experience" (www.comics.org)
Offsetdruck. - Umschlag farbig
Detaillierte Inhaltsangabe s. https://www.comics.org/issue/1304906/#1479423 (Zuletzt aufgerufen am: 17.03.2017)
Keywords: Graphzine